Merdeka Belajar Curriculum Implementation in Inclusive Schools - Rita Aryani; Siti Nuraini Purnamawati; Erfan Kurniawan (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this research was to analyze the Merdeka Belajar Curriculum implementation in inclusive schools. The method used in this research was qualitative. Data collection techniques used were observation, interviews with 17 vice principals of academic affairs, and documentation. The analytical method used is data reduction, data presentation, and conclusion. The results of research showed that from 17 schools in DKI Jakarta, the implementation of Merdeka Belajar Curriculum in inclusive schools has not run optimally, such as special education teachers in inclusive schools were forced to become homeroom teachers, the application of the curriculum was still being segregated with the weight of subjects for students with disabilities being more in special classes than in regular courses, teacher competence regarding inclusive education curricula which was still inadequate, and there was no special education teachers who handled students with special needs in the implementation of Merdeka Belajar Curriculum in inclusive schools.